Movement and physiological match demands of elite rugby league using portable global positioning systems - Waldron, M.; Twist, C.; Highton, J.; Worsfold, P.; Daniels, M. (Journal of Sports Sciences, 2011)
Twelve elite players from an English Super League club consented to participate in the present study using portable global positioning system (GPS) devices to assess position-specific demands. Distances covered at low-intensity running, moderate-intensity running, high-intensity running, very high-intensity running, and total distance were significantly (P < 0.05) lower in forwards compared with outside backs and adjustables. Metres per minute was higher in adjustables and forwards, owing to higher values for relative distance in medium-intensity running and a rise in high-intensity running from previous absolute values. Sprint distance, sprint frequency, and peak speed were higher in outside backs than both adjustables and forwards. A moderate, significant correlation (r = 0.62, P = 0.001) was apparent between session ratings of perceived exertion and summated heart rate. Results support the requirement for position-specific conditioning and provide preliminary evidence for the use of session ratings of perceived exertion as a measure of match load.